Estimating the prevalence of high-risk drug users using multi-method estimation - Rožė Perminienė; Natalja Istomina; Rimantas Stukas; Alma Molytė (Frontiers in Public Health, 2026)
Introduction When conducting studies related to drug use, researchers around the world face the challenge of obtaining the most accurate and reliable data on the extent of drug use, when direct research instruments are difficult to use (direct survey of subjects due to the illegality of the activity is not possible). Problematic high-risk drug use is especially harmful when these substances are used in risky or high-risk ways. Three drug use prevalence studies have been conducted in Lithuania (2006, 2010, 2017); therefore, the latest data on problematic high-risk drug use are extremely relevant. The aim of this study is to assess the prevalence of high-risk drug users using multi-method estimation in Lithuania using 2021 data. Results The research hypothesis—the likely increase in the number of high-risk drug users in Lithuania—was confirmed. Over the 5 years (2017–2021), the number of high-risk drug users in Lithuania increased: high-risk opioid users—by 1.6 times, injecting drug users—by 1.7 times. These indicators also increased in Lithuania’s largest cities (Vilnius, Kaunas, Klaipėda)—the most pronounced increase was observed in Vilnius. Conclusion The prevalence of high-risk drug use in Lithuania has increased significantly in recent years and is now not only similar to other European countries, but also higher than in some countries. It is also evident that Lithuania has a high number of injecting drug users. The country should be more active in increasing effective preventive and intervention measures for high-risk drug users.